Evaluation of CFD codes by comparison of numerical predictions of an air-conditioned room case study - Gaspar, Pedro Dinis (2004)
Nowadays, the advances in computer hardware and software allowed the development of a new generation of Computational Fluid Dynamics (CFD) codes which are much more user-friendly in terms of mathematical modelling, numerical techniques and presentation of results. The aim of this study is to present the evaluation and comparison between the numerical results obtained with two commercial codes, an academic one and experimental data for a of a typical ventilation case study. Therefore, the scope includes the validation of the numerical results and discussion of the potentialities, complexity and user interface of each code.